Avalanches in a numerically simulated sand dune dynamics - Sagar, , BSD; Radhakrishnan, , P; Murthy, , MBR (2003)
Avalanches of various sizes occur due to instability during sand dune dynamics. A physically viable equation to model sand dune dynamics is a first order nonlinear difference equation. To visualize the size distribution of avalanches, sand dune dynamics has been numerically simulated by changing the strength of nonlinearity parameter (lambda) that shows different impacts on dune dynamics. An equation to compute avalanche diameters, by considering the inter-slipface angles of a simulated sand dune under dynamics, is proposed. Using this equation, avalanche diameters have been computed from a dynamically changing simulated sand dune.